Decoding Virality: How Micro-Moments Drive Consumer Behavior in Social Media Marketing - Yusda, Desi Derina; Silvia, Dewi; Indriyani, Susi; Meidasari, Evi; Bakti, Umar (SAFE-Network, 2025)
This study investigates how micro moments and content virality influence purchase intention among Generation Z social media users in Indonesia. Employing a mixed methods design, it integrates quantitative survey data from 215 respondents and qualitative insights from 15 in depth interviews. Micro moments categorized as “I want to know,” “I want to go,” “I want to do,” and “I want to buy” are examined alongside content virality elements such as emotional resonance and shareability. Structural Equation Modeling (SEM) confirms that both micro moments and content virality significantly affect purchase intention, with brand engagement serving as a mediating variable. Additionally, multigroup analysis reveals that digital literacy moderates the relationship between engagement and purchase outcomes. Qualitative thematic analysis further supports these findings by revealing cognitive and emotional pathways triggered by social media interactions. The research contributes to behavioral marketing literature by offering an integrative framework that links temporal triggers, emotional content dynamics, and user competencies. Practical implications suggest marketers must design real time, emotionally engaging, and literacy aware content strategies. This study not only fills a critical gap in Southeast Asian digital consumer behavior research but also provides strategic insights for businesses targeting Gen Z on platforms like TikTok and Instagram.